Use of media and technology, academic procrastination, and academic achievement in adolescence - Türel, Yalın Kılıç; Dokumaci, Özlem (Ozgen Korkmaz, 2022)
In today’s learning society, use of media and technology affects students in all educational levels. There are a number of studies conducted among university students in this context. However, adolescents, who are sensitively exposed to the negative effects of the excessive use of media and technology, have been neglected. The aim of this study is to investigate the association among adolescents’ use of media and technology, their academic procrastination behavior, and academic achievement. This study also examines the possible mediating effect of academic procrastination behavior on the relationship between adolescents’ media and technology use and academic achievement. This quantitative study included data from 1278 middle and high school students. We collected data via a questionnaire comprising of the demographic information form, media and technology usage and attitude scale, and academic procrastination behavior scale as well as students’ grade point averages to measure students’ academic achievement. The results revealed that as media and technology usage increased, students’ academic achievement decreased. In addition, academic procrastination behavior had a mediating effect on this relationship. In other words, adolescents' media and technology use cause academic procrastination behaviour to adversely affect their academic achievement. The implications for future research and the limitations of the study were also discussed. © 2022, Ozgen Korkmaz. All rights reserved.
Keywords: Academic achievement; Academic procrastination; Adolescence; Media and technology use; Procrastination behaviour